Case Report: Spinal muscular atrophy with IgA nephropathy: a coincidence or association? - Gu, Yuxuan; Wang, Le; Yuan, Xiaoying; Han, Yanan; Han, Peitong; Cui, Jieyuan; Wang, Xinlei; Huang, Yuchan; Zhang, Lili; Li, Chunzhen (Frontiers in Pediatrics, 2026)
BackgroundSpinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder caused by biallelic loss-of-function variants of the survival motor neuron 1 (SMN1) gene on chromosome 5q13. It has been reported that SMA may affect the function of the kidneys. Here, we report a patient with co-occurrence of SMA and IgA nephropathy (IgAN).Case presentationA 14-year-old girl presented with six months of limb weakness, progressive exacerbation of symptoms of left lower limb muscle weakness; her left lower limb muscle strength decreased, and bilateral knee tendon reflexes and Achilles tendon reflexes were not elicited. The patient was diagnosed with SMA type 3 in conjunction with the results of genetic testing. The patient had proteinuria and hematuria, and a renal biopsy was performed. Considering the patient's clinical and pathological characteristics, the final diagnosis was spinal muscular atrophy combined with IgA nephropathy. To the best of our knowledge, this is the first reported case that demonstrates the coexistence of SMA and IgAN.Discussion and conclusionsThe exact mechanism of renal impairment due to SMA is not fully understood, and the combination of SMA with IgAN is extremely rare. Our report suggests that there may be a potential association between them.